Metabolic sialic acid blockade lowers the activation threshold of moDCs for TLR stimulation. Issue 4 (22nd November 2016) - Büll, Christian; Collado‐Camps, Estel; Kers‐Rebel, Esther D; Heise, Torben; Søndergaard, Jonas N; den Brok, Martijn H; Schulte, Barbara M; Boltje, Thomas J; Adema, Gosse J
Abstract : Sialic acid sugars cover the surface of dendritic cells (DCs) and have been suggested to impact several aspects of DC biology. Research into the role of sialic acids in DCs, however, is complicated by the limited number of tools available to modulate sialic acid expression. Here we report on a synthetic, fluorinated sialic acid mimetic, Ac5 3Fax Neu5Ac, which potently blocks sialic acid expression in human monocyte‐derived DCs (moDCs). Sialic acid blockade enhanced the responsiveness of moDCs to Toll‐like receptor (TLR) stimulation as measured by increased maturation marker expression and cytokine production. Consequently, the T‐cell activation capacity of Ac5 3Fax Neu5Ac‐treated moDCs was strongly increased. In addition to sialic acids, moDCs also expressed the sialic acid‐binding immunoglobulin‐like lectins (Siglecs) ‐3, ‐5, ‐7, ‐9 and ‐10, immune inhibitory receptors recognizing these sialic acids. Treatment with Ac5 3Fax Neu5Ac abrogated putative cis and trans interactions between sialic acids and Siglec‐7/‐9. Together, these data indicate that sialic acids limit the activation of moDCs via the TLR pathway, potentially by interacting with Siglec‐7 or Siglec‐9. Metabolic sialic acid blockade with Ac5 3Fax Neu5Ac could therefore potentially be used to generate more potent DC‐based vaccines for induction of robust anti‐viral or anti‐tumor immune responses.